Military and Civil Society in Conflict Areas: A Sociological-Legal Study on the Dynamics of Power and Legitimacy (Pusat Riset dan Inovasi Nasional, 2026)
This article examines the complex interactions between the military and civil society in regions affected by conflict, approached from a sociological-legal perspective. The study seeks to understand how military power influences civil society, the ways in which legal and social legitimacy are established, and how local communities respond to military presence and control. Employing a qualitative case-study methodology, the research utilized in-depth interviews with community members and military personnel, extensive field observations, and detailed analysis of relevant legal documents. The findings reveal that military power structures significantly impact civil rights, security, and social dynamics, with interactions ranging from cooperative engagement to open conflict. Furthermore, the legitimacy of military actions is closely linked to factors such as operational performance, transparency, accountability, and social acceptance by local populations. Based on these insights, the article argues for the importance of improving communication channels between military forces and communities, integrating formal legal frameworks with local norms and practices, and actively involving community members in security and governance programs. These measures are proposed as strategies to enhance the legitimacy of military operations, reduce conflict, and promote long-term social stability. The study contributes to the broader understanding of civil-military relations by highlighting the sociological and legal dimensions of military influence in conflict-affected areas.